PENERAPAN UI/UX SISTEM INFORMASI SPONSORSHIP EVENT PT INDOSAT OOREDOO DENGAN METODE DESIGN THINKING - Kahar, Novhirtamely; Puspitorini, Sukma; Brilian Iswandi, Anjel (LP2M Universitas Nurdin Hamzah, 2023)
Developing a UI/UX Implementation Application for the PT Indosat TBK Sponsorship Event Information System using the Design Thinking Method in a systematic and structured manner so that it can help Admin and Marketing Communication in recording and monitoring Sponsorship Events within a certain period. As well as a structured database system that makes it easier for admin performance to be effective and efficient. This is because currently there is no media available to process PT Indosat event sponsorships. With a database aimed at managing the application database, it can be built properly using PHP. This system has a small scale and involves only a few people in the system, namely marketing, admin and users. The aim of implementing the Pt Indosat TBK Event Sponsorship Information System UI/UX using the Design Thinking Method makes it easier to manage proposal data and create reports. This Information System inputs admin, marketing, user, proposal, micro cluster and agency data. Create an account for users so they can see the proposal status after inputting proposal data. If the proposal status is approved, then print proof of sponsorship letter for the user, so that you get admin, marketing proposal data reports and data reports per status. This application was built using Phpmyadmin, Cascading Style Sheet, Hypertext Markup Language. It is hoped that it can help Indosat in event sponsorship.